Bridging the Gaps between Knowledge and Needs: Sociolinguistics Materials Based on Project-Based Learning - Ismail, Hijril (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2022)
Sociolinguistics can help people better understand the use of English in specific social environments. Still, there have been limited studies on the crucial aspects of teaching and learning Sociolinguistics to gain optimum learning outcomes. This present research aims to analyse models of EFL Sociolinguistics materials based on project-based learning required by students and lecturers. A quantitative method was applied in this study, employing a questionnaire and structured interview to collect data from 57 students and three instructors of the English Education Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Mataram. The results revealed that students and lectures required teaching materials with clear objectives embodied in 11 topics, from Language Variations to Language and Ideology completed with evaluations after each topic, exercises for individuals or groups, and project-based learning, which can be employed in teaching EFL Sociolinguistics. Therefore, designing a model of teaching materials for EFL Sociolinguistics based on Project-based learning is necessary to load these findings. The findings of this study are useful for educators and stakeholders who want to design EFL Sociolinguistics teaching materials. This study has the potential to bridge the gap by providing knowledge about the needs of students and educators as well as recommendations for follow-up in designing EFL Sociolinguistics teaching materials.